2023
DOI: 10.15403/jgld-4962
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Intravenous Lidocaine Infusion on Postoperative Outcome and Neutrophil-to-Lymphocyte Ratio in Colorectal Cancer Patients. A Pilot Study

Alexandru Leonard Alexa,
Andra Ciocan,
Florin Zaharie
et al.

Abstract: Background and Aims: In the last years increasing scientific evidence drew attention on the potential effects of anesthetic drugs on postoperative outcome in cancer patients. Local anesthetics, especially lidocaine, have been intensively studied in relation with postoperative outcome in colorectal cancer patients. Our study objectives were to investigate the effects of perioperative intravenous lidocaine infusion on neutrophil-to-lymphocyte ratio and short-term postoperative outcome. Additionally, we also look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Alexa et al . observed that intravenous lidocaine infusion decreases the risk of cancer recurrence in colorectal cancer patients [ 37 ]. Notwithstanding, a similar intervention did not improve overall survival rates in patients with pancreatic cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexa et al . observed that intravenous lidocaine infusion decreases the risk of cancer recurrence in colorectal cancer patients [ 37 ]. Notwithstanding, a similar intervention did not improve overall survival rates in patients with pancreatic cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have corroborated the anti-tumorigenic effect of lidocaine [34][35][36]. Alexa et al observed that intravenous lidocaine infusion decreases the risk of cancer recurrence in colorectal cancer patients [37]. Notwithstanding, a similar intervention did not…”
Section: Plos Onementioning
confidence: 99%
“… 197 Colo-rectal Lidocaine (intravenous) One hundred and fifty patients randomized to receive lidocaine (n = 77) or not (n = 73). Decreased rate of recurrence ( p = .03) but no impact on 1-year survival ( p = .22) 200 ENT Ropivacaine (epidural) Thirty patients randomized to receive epidural or not. Reduction in blood glucose ( p = .0153) and cortisol ( p = .0074) 118 Gastric Ropivacaine (epidural) Fifty patients randomized to receive epidural or not.…”
Section: Clinical Investigationmentioning
confidence: 99%
“… 199 In the study by Alexa et al ., a significant reduction in recurrences was observed after the intravenous injection of lidocaine during colectomy. 200 After hepatectomy, the analgesic infusion of ropivacaine (bolus plus continuous injection through a local catheter) improved postoperative survival compared to the use of tramadol and fentanyl to control surgical pain. 201 The perfusion of ropivacaine through an intraperitoneal catheter minimized the time to initiate adjuvant chemotherapy after ovariectomy compared to the control group.…”
Section: Clinical Investigationmentioning
confidence: 99%
“…lidocaine postoperatively decreased the NLR after breast cancer surgery [136], while Alexa et al did not find an influence of i.v. lidocaine at 24 h after colorectal surgery [137]. An erector spinae plane block (ESPB) significantly decreased the NLR after spine surgery [138].…”
Section: Anesthetic Drugs and The Nlrmentioning
confidence: 99%